Efeito de uma matricriptina derivada do colágeno I na trombose e remodelamento vascular na aorta abdominal de camundongos : Effect of a collagen I derived matricryptin in thrombosis and vascular remodeling on mice abdominal aorta - Dal Pozzo, Caroline Fernanda Sanches, 1994- (2018)
Orientador: Cristina Pontes Vicente